KEBIJAKAN NASIONAL TERHADAP PEMBANGUNAN BERWAWASAN LINGKUNGAN - Poerwanti Hadi Pratiwi * (Dimensia: Jurnal Kajian Sosiologi, 2008)
This article is going to discuss about national policy in the development of environment concept, or known as Ecodevelopment. The focus of this article will be more illuminated on the decreasing of causal factor of development in Indonesia. Ecodevelopment strategy consist of especially elements are community different from others, specific cultural values, live in specific territories, and specific resources too. Because of ecodevelopment strategy goals are reform and develop specific conditions, not create "development" in term GNP (Gross National Product) or another abstraction. Ecodevelopment can be applied in various local ecosystem according cultural and ecology data from specific community. Now, Indonesia active doing development in all aspect, be up against some problems of ecology acpect. Ecodevelopment policies are approach of resources management, the welfare meaning, responsibility from inter-generation, and factor of problems. Keywords: Ecodevelopment, National Policy, Environment